Simfonična ustvarjalnost Rista Savina - Barbo, Matjaž (Muzikološki zbornik, 2012)
Orchestral works represent a distinctly minor part of Savin's compositional output and are written around the chronological edges of his creative span, atthe beginning of his activity as a composer and later towards the end of his life. Nevertheless a study of these compositions demonstrates how Savin gradually improved his compositional technique and became a master in instrumentation.
Keywords: Savin, Risto; simfonična glasba; slovenska glasba; slovenski skladatelji